Empowering the children's and women's forum as an effort to protect children and women from violence - Ratri Novita Erdianti; Wasis Suprayitno; Sholahuddin Al-Fatih (Universitas Muhammadiyah Malang, 2023)
Many cases occur in Indonesia that show children and women have become victims of violence, one of which is domestic violence. There are many cases in the community of children and women who experience physical, psychological, sexual violence and neglect in the family, especially in the household. This community services uses FGD method to strengthen the children's and women's forum. The findings of this community services found that change is a must, so that in this case the government needs to make efforts to educate the public to be more open and able to take care of themselves to avoid becoming victims of violence, especially in the household. This community services take place in Dadaprejo, Batu, Esat Java. As a result, the Women and Children Forum is an important tool to be carried out as a means of communication that is implemented to prevent women and women from becoming victims of violence.